The effects of plyometric jump training on jump and sport-specific performances in prepubertal female swimmers - Senda Sammoud; Yassine Negra; Raja Bouguezzi; Younes Hachana; Urs Granacher; Helmi Chaabene (Elsevier, 2021)
Background/objective: Dry land-training (e.g., plyometric jump training) can be a useful mean to improve swimming performance. This study examined the effects of an 8-week plyometric jump training (PJT) program on jump and sport-specific performances in prepubertal female swimmers. Methods: Twenty-two girls were randomly assigned to either a plyometric jump training group (PJTG; n = 12, age: 10.01 ± 0.57 years, maturity-offset = -1.50 ± 0.50, body mass = 36.39 ± 6.32 kg, body height = 146.90 ± 7.62 cm, body mass index = 16.50 ± 1.73 kg/m2) or an active control (CG; n = 10, age: 10.50 ± 0.28 years, maturity-offset = -1.34 ± 0.51, body mass = 38.41 ± 9.42 kg, body height = 143.60 ± 5.05 cm, body mass index = 18.48 ± 3.77 kg/m2). Pre- and post-training, tests were conducted for the assessment of muscle power (e.g., countermovement-jump [CMJ], standing-long-jump [SLJ]). Sport-specific-performances were tested using the timed 25 and 50-m front crawl with a diving-start, timed 25-m front crawl without push-off from the wall (25-m WP), and a timed 25-m kick without push-off from the wall (25-m KWP). Results: Findings showed a significant main effect of time for the CMJ (d = 0.78), the SLJ (d = 0.91), 25-m front crawl test (d = 2.5), and the 25-m-KWP (d = 1.38) test. Significant group × time interactions were found for CMJ, SLJ, 25-m front crawl, 50-m front crawl, 25-m KWP, and 25-m WP test (d = 0.29-1.63) in favor of PJTG (d = 1.34-3.50). No significant pre-post changes were found for CG (p > 0.05). Conclusion: In sum, PJT is effective in improving muscle power and sport-specific performances in prepubertal swimmers. Therefore, PJT should be included from an early start into the regular training program of swimmers.